Insecurity and Attainment of Sustainable Development Goals 1 and 2 in Nigeria - Nwagbo, Samuel N. C.; Francis, Azubuike Callistus; Ezeakoafor, Abraham (Advances in Social Sciences Research Journal, 2025)
This study interrogated how insecurity affects the attainment of Sustainable Development Goals 1 (Hunger) and 2 (Poverty) in Nigeria. This is based on the target to end hunger and poverty by 2030 and the precarious situation of these two important phenomena in Nigeria’s development trajectory. Hunger and poverty are ugly socio-economic realities that most of the Nigerian populace, regardless of age, gender, religion and region, are confronted with. The study was anchored on Maslow’s theory of Needs and Systems Theory. Data was gathered through documentary sources of literature, and it was analysed using an explanatory method of data analysis. The study found that insecurity has made the efforts of the United Nations (UN) through Sustainable Development Goals (SDGs) to end hunger and poverty in Nigeria by 2030 unattainable. The insecurity situation in Nigeria is aggravated by the high level of unemployment, especially among the youth and the non-availability of basic infrastructure to drive development. It is recommended that youth unemployment must be curbed through investment in the critical infrastructure, like roads, power, schools, health and social justice. This will help to engage the teeming unemployed youths who fall prey and are lured into activities that constitute security threats. Also, International Development Institutions should engage the Nigerian government in ensuring implementation of programmes and projects that will end to hunger and poverty, especially in agriculture, entrepreneurship, and technology. The security architecture of Nigeria should be restructured to engage the locals (state police, vigilante) in taking active decisions concerning the security of their immediate environment without undue restrictions from the centre.